A new species of Paralamyctes (Chilopoda: Lithobiomorpha: Henicopidae) from southern Chile - Edgecombe, Gregory D. (Zootaxa, 2003)
Paralamyctes wellingtonensis n. sp. occurs further south in Chile than its sister species, P. chilensis (Gervais in Walckenaer & Gervais, 1847). The new species, from Isla Wellington and Magallanes, is identified by distinctive female gonopods.